CHARM: Collaborative Host and Accelerator Resource Management for GPU Datacenters - Zhang, Wei; Fu, Kaihua; Zheng, Alvin; Chen, Quan; Li, Chao; Zheng, Wenli; Guo, Minyi (ICCD 2021, 2021)
Emerging latency-critical (LC) services often have both CPU and GPU stages (e.g. DNN-assisted services) and require short response latency. Co-locating best-effort (BE) applications on the both CPU side and GPU side with the LC service improves resource utilization. However, resource contention often results in the QoS violation of LC services. We therefore present CHARM, a collaborative host-accelerator resource management system. CHARM ensures the required QoS target of DNN-assisted LC services, while maximizing the resource utilization of both the host and accelerator. CHARM is comprised of a BE-aware QoS target allocator, a unified heterogeneous resource manager, and a collaborative accelerator-side QoS compensator. The QoS target allocator determines the time limit of an LC service running on the host side and the accelerator side. The resource manager allocates the shared resources on both host side and accelerator side. The QoS compensator allocates more resources to the LC service to speed up its execution, if it runs slower than expected. Experimental results on an Nvidia GPU RTX 2080Ti show that CHARM improves the resource utilization by 43.2%, while ensuring the required QoS target compared with state-of-the-art solutions.